2020
DOI: 10.1111/cns.13437
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pharmacotherapeutics for patients comorbid with alcohol use disorders and depressive symptoms—A bayesian network meta‐analysis

Abstract: Alcohol use disorders (AUD), including alcohol abuse and alcohol dependence, are common psychiatric disorders contribute greatly to the burden of society. 1 Alcohol-related diseases are one of the leading risk factors of disability and mortality, causing about 3.3 million deaths around the world and taking account for 5.1% of the global burden of disease according to the report of WHO. 2 Depression is a highly prevalent mental illness and is one of the important causes of premature deaths. About 350 million pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 106 publications
(282 reference statements)
0
37
0
Order By: Relevance
“…In a meta-analysis of 15 head-to-head RCTs comparing SSRIs and SNRIs showed that SNRIs had statistical significance over SSRIs in treating MDD ( 47 ); these studies did not include participants with AUD. In the AUD literature, a recent network meta-analysis of 68 RCTs consisting of 5,890 patients with AUD comparing different classes of antidepressants including SSRIs (e.g., paroxetine, citalopram, escitalopram, fluoxetine, and sertraline), NRIs (e.g., venlafaxine and viloxazine), and tricyclic antidepressants (e.g., desipramine, imipramine, amitriptyline) showed that NRIs demonstrated the best efficacy and were superior to SSRIs in reducing scores of depression scales ( 48 ). However, in that study, desipramine was categorized as a tricyclic antidepressant, which did not show any statistically significant difference in both depression and AUD outcomes when compared to SSRIs (including paroxetine) ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of 15 head-to-head RCTs comparing SSRIs and SNRIs showed that SNRIs had statistical significance over SSRIs in treating MDD ( 47 ); these studies did not include participants with AUD. In the AUD literature, a recent network meta-analysis of 68 RCTs consisting of 5,890 patients with AUD comparing different classes of antidepressants including SSRIs (e.g., paroxetine, citalopram, escitalopram, fluoxetine, and sertraline), NRIs (e.g., venlafaxine and viloxazine), and tricyclic antidepressants (e.g., desipramine, imipramine, amitriptyline) showed that NRIs demonstrated the best efficacy and were superior to SSRIs in reducing scores of depression scales ( 48 ). However, in that study, desipramine was categorized as a tricyclic antidepressant, which did not show any statistically significant difference in both depression and AUD outcomes when compared to SSRIs (including paroxetine) ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of the ve studies on disul ram, three very low qualities found a signi cant effect, for increase in AUD remission rate among people with comorbid depression compared with control (OR 5.00, 95% CI 1.97 to 12.95), acamprosate, antipsychotics, bromocriptine, lithium, naltrexone, and SSRI [74]; abstinence at 12 weeks follow-up (SMD − 0.32, 95% CI − 0.56 to − 0.07) but not for heavy drinking days (SMD − 0.44, 95% CI − 0.94 to 0.06) [96]. Similarly, evidence from was inconclusive for antiepileptics, which showed a signi cant improvement in AUD remission rate among individuals with comorbid depression when compared to control, bromocriptine and lithium in a network meta-analysis of odds ratios, but not when compared to control using standardised mean difference (SMD − 0.70, 95% CI − 2.05 to 0.65) [74], and for varenicline, which showed a signi cant effect for alcohol consumption (SMD − 0.37, 95% CI − 0.66 to − 0.07) but not heavy drinking days (SMD − 0.14, 95% CI − 0.33 to 0.05 [85]. Certainty in the evidence for each of the other pharmacological interventions was rated as very low, due to high risk of bias and imprecision in many studies, resulting from very wide con dence intervals and/or sample sizes less than 100.…”
Section: Screening Brief Intervention and Referral To Treatment (Sbir...mentioning
confidence: 99%
“…It should be noted that total number of participants for both upentixol and quetiapine was below 100. For antipsychotics as a whole, a network meta-analysis of AUD remission rate among people with comorbid depression found no signi cant effect compared with control (OR 0.97, 95% CI 0.30 to 3.22) and suggested that antipsychotics are inferior to disul ram (OR 0.19, 95% CI 0.04 to 0.9) [74]. However, whilst there was no effect on relapse, another review found a signi cant improvement in ratio of abstinent to drinking days when compared with placebo at 3-12 months follow-up (RR 0.17, 95% CI 0.01 to 0.33) [77].…”
Section: Screening Brief Intervention and Referral To Treatment (Sbir...mentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials have reported a higher prevalence of depressive symptoms in patients with alcohol dependence. [1][2] Alcohol abuse and alcohol dependence are common psychiatric illnesses; according to WHO, they are responsible for about 3.3 million deaths worldwide. 3 It is estimated that about 350 million people suffer from depression, and out of these, nearly one million of them commit suicide each year.…”
Section: Introductionmentioning
confidence: 99%